Outcome of keratolimbal allograft transplantation with deep anterior lamellar keratoplasty for bilateral limbal stem cell deficiency - Li, Zongyuan; Yang, Kunkun; Zhou, Yannan; Wu, Tengyun; Zhang, Hongtao; Yang, Qinghua; Wang, Qun; Huang, Yifei; Wang, Liqiang (Frontiers in Medicine, 2022)
Objectives: To evaluate and compare the outcome of keratolimbal allograft (KLAL) transplantation with or without deep anterior lamellar keratoplasty (DALK) for bilateral severe limbal stem cell deficiency (LSCD). Methods: This retrospective review included forty-nine eyes of 46 patients who underwent KLAL transplantation at the Department of Ophthalmology of Chinese PLA general hospital, 2009-2020, for bilateral severe LSCD were examined for corneal clarity and corneal scarring to determine whether to combine DALK with KLAL transplantation. Preoperative information, surgical decision tree, surgical procedures, and postoperative data were collected for each eye. Results: All patients had preoperative severe or total LSCD. Twenty-four eyes underwent KLAL transplantation only, twenty-five KLAL transplantation plus DALK. The mean follow-up was 46.80±31.22 months (18-158 months). Overall KLAL survival (with or without DALK) was 71.43% at the final follow-up (KLAL-only 66.67%, KLAL-DALK 76%). Kaplan–Meier survival analysis showed that the 3-year survival probability of all grafts was 70.53% ± 10.89% (KLAL-only 64.86%±10.11%, KLAL-DALK 75.79%±8.62%). The proportion of BCVA≥20/200 eyes among all KLAL transplantations increased from 11 eyes (22.45%) preoperatively to 25 eyes (51.02%) after 1 year and 24 eyes (48.98%) at the last follow-up (P=0.01). The proportion of BCVA≥20/200 eyes in the KLAL-DALK group increased significantly (P=0.04), from 16.0% at baseline to 48.0% after 1 year to 44.0% at the last follow-up. Seventeen eyes (34.69%) had postoperative complications. Conclusions: KLAL-DALK is an effective option to restore a stable ocular surface and visual acuity rapidly in patients with bilateral, late-stage, severe LSCD.